Cultural Transfer in the Habsburg Empire. Croatia and German-Langugage Culture from a Postcolonial Perspective - Bobinac, Marijan (2014)
Two outstanding moments from the history of the Croatian theatre (the beginning of national-language theatre and the end of the German-language theatre in Zagreb around the middle of the 19th century) are used here in order to show how painfully cultural asymmetry in relation to the centre was felt by the small nations in the Monarchy, and how emphatic they tried to overcome their position.
Projekt MZOS
ENG